Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Kepatuhan Wajib Pajak - Afrizal Tahar; Arnain Kartika Rachman (Journal of Accounting and Investment, 2014)
This study aims to analyze the Influence of Internal Factors and External Factors on Taxpayer Compliance. Internal factors such as religious understanding and awareness, while external factors that corruption committed by unscrupulous tax, public services, and advertising. Objects in this study is Jebres Surakarta and research subject is an individual taxpayer. This study has a sample of 57 respondents to the taking of convenience. The analytical tool used SPSS 19.0. Based on the analysis conducted, the results showed that influence awareness of tax compliance and the other factors such as; corruption committed by unscrupulous tax, religious understanding, public services, and advertising does not affect tax compliance.